1996
DOI: 10.1159/000188845
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Statistical Moments for Desferrioxamine and Its Iron and Aluminium Chelates: Contribution to Optimisation of Therapy in Uremic Patients

Abstract: We investigated the best time of administration of desferrioxamine (DFO) with respect to the dialysis session, using the approach of the stochastic dynamic system, integrated with the classical pharmacokinetic models. In the 6 patients studied, the mean arrival times of DFO, aluminoxamine (AlO) and ferrioxamine (FO) were, respectively, 193, 1,350 and 126 min, the mean residence times were 1,048, infinite, 1,190 min, respectively. AlO serum levels reach steady state in a mean time of 7 h and 22 min and remain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is well established that despite DFO administration, if aluminum is bound to transferrin, it is neither dialyzable nor accessible to DFO [31]. One study found that only 1 % of all available serum aluminum was chelated as aluminoxamine (AlO), highlighting the importance of transferrin and other endogenous binding proteins [32]. Third, the potential toxicities of the unbound DFO chelator, as well as the toxicities of both chelates-AlO and ferrioxamine (FO)-must be anticipated.…”
Section: Aluminum Chelators and Chelation Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that despite DFO administration, if aluminum is bound to transferrin, it is neither dialyzable nor accessible to DFO [31]. One study found that only 1 % of all available serum aluminum was chelated as aluminoxamine (AlO), highlighting the importance of transferrin and other endogenous binding proteins [32]. Third, the potential toxicities of the unbound DFO chelator, as well as the toxicities of both chelates-AlO and ferrioxamine (FO)-must be anticipated.…”
Section: Aluminum Chelators and Chelation Considerationsmentioning
confidence: 99%
“…Third, the potential toxicities of the unbound DFO chelator, as well as the toxicities of both chelates-AlO and ferrioxamine (FO)-must be anticipated. AlO and FO following DFO administration may persist for long periods, especially in kidney disease [32,33].…”
Section: Aluminum Chelators and Chelation Considerationsmentioning
confidence: 99%
See 1 more Smart Citation